Maternal Inulin Supplementation Alters Hepatic DNA Methylation Profile and Improves Glucose Metabolism in Offspring Mice - Zhang, Qian; Xiao, Xinhua; Zheng, Jia; Li, Ming; Yu, Miao; Ping, Fan; Wang, Tong; Wang, Xiaojing (Frontiers in Physiology, 2020)
Scope: As a prebiotic, inulin may have a protective effect on glucose metabolism. However, the mechanism of inulin treatment on glucose intolerance in offspring exposed to a maternal high-fat diet is still not clear. Here, we examined the hepatic DNA methylation profile to determine how maternal inulin supplementation modified glucose metabolism in offspring mice. Procedures: Female mice were fed a high-fat (HF) diet, control diet (CON) or a high-fat diet with inulin supplementation (HF-inulin) during gestation and lactation. Upon weaning, pup livers were obtained. A hepatic genome DNA methylation array was performed. Results: Pups exposed to a maternal HF diet exhibited glucose intolerance and insulin resistance. Maternal inulin treatment moderated glucose metabolism. A DNA methylation array identified differentially methylated regions associated with 970 annotated genes from pups exposed to a HF diet in response to maternal inulin treatment. In particular, the wingless-type MMTV integration site family member 5A (Wnt5a) gene was hypermethylated, and the phosphatidylinositol-4-phosphate 3-kinase catalytic subunit type 2 alpha (Pik3c2a), phosphatidylinositol-4-phosphate 3-kinase catalytic subunit type 2 beta (Pik3c2b), and phosphoinositide-3-kinase regulatory subunit 2 (Pik3r2) genes were hypomethylated in inulin-treated pups. Consistently, hepatic Wnt5a gene expression was reduced and Pik3c2a, Pik3c2b, and Pik3r2 gene expression was increased in the inulin group. Conclusion: Maternal inulin treatment improved glucose intolerance by changing DNA methylation and gene expression of Wnt5a and Pi3k in mice exposed to a maternal HF diet.